Regulation of gene expression by N(6)-methyladenosine in cancer - Liu, Jun (Trends Cell Biol, 2019)
As the most abundant mRNA modification in eukaryotic cells, N(6)-methyladenosine (m(6)A) has recently emerged as an important regulator of gene expression. m(6)A modification can be deposited by m(6)A methyltransferases, removed by m(6)A demethylases and recognized by different reader proteins. Numerous lines of evidence have shown that m(6)A methylation plays critical roles regulating gene expression in development and disease. In this review, we summarize the molecular and cellular function of m(6)A and highlight some key results which demonstrate the role of m(6)A in various cancers. Finally, we discuss future directions for research into m(6)A and its effects in cancer and the potential for targeting RNA modification in cancer treatment.